Peran Orang Tua Dalam Penanaman Pendidikan Karakter Kejujuran Bagi Anak Remaja Perspektif Al-Qur’an Surah Luqman Ayat 16 - Izzan, Ahmad; Alfatihah, Dhyan (STAI Al-Musaddadiyah Garut, 2024)
Honesty is an ability an talent prossesed by a person to always say and behave in accordance with existing circumstances without exaggerating it, in this case, a teenage child needs guidance from his parents, because parents are the first person responsible for educating their children to develop into a complete adult human being. However, instilling honesty in children is not easy thing, especially in teenagers who are currently affected by the era of globalization. Therefore, this study aims to describe The Role Of Parents In Installing Honesty Character Education For Teenagers From The Perspective Of Alqur’an Surah Luqman Verse 16. Then, the method use in this research is descriptive qualitative. The data collection technique used in this research is documentation study. The data analysis technique used by research is in the form of content analysis and uses analaysis from several interpretations. Based on the results of the study, instilling of honesty character education for teenagers is carried out using exemplary and habituation starategies and the fulfillment of honesty character indicators. According to several interpretations that have been studied, Luqman gives advice to his son to always do good and not hide anything from anyone especially from Allah, because Allah is the most subtle and meticulous. In the Qur’an surah Luqman verse 16 there is a description of a father who loves his son so much that he never stops giving advice, seeing this, of course it is very clear here that the role of parents is very necessary in terms of instilling honesty character education for teenagers. Keywords : parental role, honesty character, teenagers.